PENGARUH ATRIBUT PRODUK, CITRA MEREK, WORD OF MOUTH (WOM), DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN (Studi Pada Pengguna iPhone Merek Apple di Kota Pontianak) - admin, Syarifah Andiani Kusuma B11112102 (Jurnal Manajemen Update, 2016)
This research aims for test and analyze the influence of product attribute, brand image, word of mouth (wom) and lifestyle of buying decision iPhone Merek Apple in Pontianak. This research is quantitative. Population of the research are Pontianak all of iPhone user. The sampel of 100 respondents were selected by purposive sampling, The criteria of the sample of respondents with a minimum age of 17 years, respondents as buyers and purchase decision an iPhone of Apple brand, and the respondent as an iPhone of Apple brand users with minimal use for 1 year. Data processing techniques using multiple linear regression analysis. The research findings prove that the variables product attribute, brand image, and lifestyle have a significant positive effect on buying decision, while variable of word of mouth has no significant positive effect on buying decision. Predictive capability of four variabels on repurchase intention is 53% while the remaining 47% was influenced by other factors not included in the research model. Keywords : product attribute, brand image, word of mouth, lifestyle, buying decision Â  Â  Â